Kondo effect in double quantum dots with ferromagnetic RKKY interaction. (14th November 2016) - Pan, Lei; Wang, YuanDong; Li, ZhenHua; Wei, JianHua; Yan, YiJing
Abstract: We study Kondo effect in parallel-coupled double quantum dots with ferromagnetic Ruderman–Kittel–Kasuya–Yoshida (RKKY) interaction, by using the exact and nonperturbative hierarchical equations of motion approach. We construct the phase diagram in the parameter plane of the inter-dot coupling t and the ferromagnetic exchange interaction J ( J − 4 t 2 / U plane). Three different ground states, the Kondo singlet, spin singlet and S = 1 Kondo, are determined in the diagram. We find the ferromagnetic coupling will raise the Kondo peak in the area of finite hopping t which is called ' J -enhanced Kondo effect'. Another enhancement of the Kondo effect by t (' t -enhanced Kondo effect') at J = 0 is also presented. By checking the electron–electron interaction self-energy and magnetic susceptibility, we verify the ground state at large J is an under-screening Kondo state composed of a Fermi liquid with a residual spin 1/2, which is consistent with the 'singular Fermi liquid state' in the literature.